2017
DOI: 10.5005/jp-journals-10050-10066
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections in a Rural Teaching Hospital of North India

Abstract: Aims and objectives: Surgical site infections (SSIs) are one of the most important causes of health care-associated infections. Understanding SSI reduces the social and economic burden of a hospital and society. In this context, we evaluated the various aspects of SSI in our institution, Rohilkhand Medical College & Hospital (RMCH), which is a tertiary care teaching hospital in rural Uttar Pradesh in North India. Materials and methods:This prospective study was conducted in the Department of General Surgery, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…In studies of Patel Sachin et al and Rajesh et al the incidence of SSI ranged from 15% to 25%. 4,5 In a study by Ansul et al 13% were male and 12% were female. 6 Highest incidence of SSI was observed in patients aged 50 years or more (44.34%) and lowest rate in the group 13-19 years and the incidence was high when associated with co-morbidities, in our study, which is similar to studies done by Narsinga Rao Bandaro et al and Keswani et al 7,8 Duration of operation was found to be an important risk factor in the development of SSI in this study with highest 63.33% cases where the operation lasted for>120 minutes.…”
Section: Discussionmentioning
confidence: 94%
“…In studies of Patel Sachin et al and Rajesh et al the incidence of SSI ranged from 15% to 25%. 4,5 In a study by Ansul et al 13% were male and 12% were female. 6 Highest incidence of SSI was observed in patients aged 50 years or more (44.34%) and lowest rate in the group 13-19 years and the incidence was high when associated with co-morbidities, in our study, which is similar to studies done by Narsinga Rao Bandaro et al and Keswani et al 7,8 Duration of operation was found to be an important risk factor in the development of SSI in this study with highest 63.33% cases where the operation lasted for>120 minutes.…”
Section: Discussionmentioning
confidence: 94%
“…Naveen et also found that majority (64.44%) of the cases belonged to 18-30 years group. [2] 30.7% of the cases were emergency and 69.3% were elective surgeries. 11.8% of the cases suffered from surgical site infection.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Abbey et al found that SSI was seen in 3.56% of clean wounds, 9.58% of clean contaminated wounds, 22.06% of contaminated and 53.45% of dirty wounds. [2] Deep SSI was more commonly seen in contaminated and dirty wounds. However, this difference was not significant statistically (p=0.78).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported SSI from rural teaching hospital to be as high as 27.7% for emergency surgeries and overall 8.67% for all surgeries. 6 With its high incidence, particularly in low resource setting like rural India, SSI places a burden on both patients and healthcare systems.…”
mentioning
confidence: 99%